2016
DOI: 10.3109/0886022x.2016.1165119
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-206 and its down-regulation of Wilms’Tumor-1 dictate podocyte health in adriamycin-induced nephropathy

Abstract: Background: Focal segmental glomerulosclerosis (FSGS) is a frequent and severe glomerular disease characterized by destabilization of podocyte foot processes. Emerging evidence suggests that microRNAs play crucial roles in podocyte homeostasis. The aim of the present study was to determine the role of miR-206 in podocyte injury and to elucidate the mechanisms responsible for the damage to podocyte. Methods: FSGS nephropathy model was induced by a single intravenous injection of Adriamycin (ADR) in BALB/c mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 22 publications
(25 reference statements)
0
9
0
Order By: Relevance
“…However, the onco-driving role of SYNPO needs more evidence to support it, because there are some controversial findings. For example, miR-206 was reported to be up-regulated in murine nephropathy, which causes severe podocyte injury and inhibits the expression of WT1 and SYNPO (Guo et al, 2016). Our results, for the first time, highlight that SYNPO can be a risk carcinogenic gene in WT.…”
Section: Discussionmentioning
confidence: 56%
“…However, the onco-driving role of SYNPO needs more evidence to support it, because there are some controversial findings. For example, miR-206 was reported to be up-regulated in murine nephropathy, which causes severe podocyte injury and inhibits the expression of WT1 and SYNPO (Guo et al, 2016). Our results, for the first time, highlight that SYNPO can be a risk carcinogenic gene in WT.…”
Section: Discussionmentioning
confidence: 56%
“…Consistent with this view, another study demonstrates that miR-206 is upregulated in ADR models and promotes podocyte injury via downregulation of WT1. 38 In addition, miRNA-193a is implicated in mediating WT1 depletion in FSGS, 19 supporting the possibility that targeting WT1 for depletion by miRNAs is common feature of proteinuric kidney diseases.…”
Section: Discussionmentioning
confidence: 95%
“…Wu et al also demonstrated that miR-30s were consistently downregulated in podocytes of FSGS patients and PANtreated rats, and identified that downregulation of miR-30s results in calcium/calcineurin signaling activation, thus leading to podocyte injury in FSGS (Wu et al, 2015). In addition, other studies have also reported the involvement of some other dysregulated miRNAs in FSGS, such as miR-135a (Yang et al, 2017), miR-155 (Ramezani et al, 2015), miR-206 (Guo et al, 2016), miR-150 (Qi et al, 2020), miR-106a (Xiao et al, 2018) and miR-146-5p (Williams et al, 2022).…”
Section: Mirnas In Focal Segmental Glomerulosclerosismentioning
confidence: 93%